BUILDING A HAPPY HOUSEHOLD: A MODEL OF HUSBAND AND WIFE RELATIONSHIP AND ITS IMPLEMENTATION IN THE FAMILY LIFE OF TABLIGH CONGREGATION. - Faizal, Liky; Nur, Efa Rodiah (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to analyze the relationship model of married couples in Tabligh Jama'ah in Bandar Lampung City and Metro City. And to explore the actualization of the rights and obligations of married couples in maintaining family harmony in the tabligh congregation of Bandar Lampung City and Metro City. This field research intensively examines how the husband and wife relationship model in the family of tabligh congregation in Bandar Lampung City and Metro City. Data were collected using observation, interview, and documentation methods. The research informants consisted of six families. The data analysis technique used in this research is qualitative data analysis. Based on the results of the study, it was found that the husband and wife relationship model in tabligh congregation in Bandar Lampung City and Metro City is that the husband in the tabligh congregation family is absolutely the leader of the household, and this is also by Marriage Law No.1 of 1974 article 31 and Compilation of Islamic Law article 79. And the actualization of the rights and obligations of married couples in maintaining the household. The actualization of the rights and obligations of spouses in preserving family harmony in tabligh congregation Bandar Lampung City and Metro City includes 3 things, namely the fulfillment of alimony which is the right of the wife, decision making which is the right of both worshipers, as well as maintenance and protection.